Board of Commissioners' Proportion, Green Innovation, and Carbon Disclosure in Enhancing Firm Value: The Role of Firm Size - Cintia Lady Anggraini; Juniati Gunawan (Jurnal Akuntansi)
Purpose - This study aims to examine the impact of the proportion of the board of commissioners, green innovation, and carbon emission disclosure on firm value, with firm size as a moderating variable, in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Design/methodology/approach - This study is a quantitative research using secondary data, which are processed and published. The population in this study consists of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The research data include 32 companies observed over four years, totaling 128 samples selected through purposive sampling technique. The data analysis techniques employed in this study include classical assumption tests, determination coefficient tests, simultaneous tests, and t-tests using EVIEWS 12 software . Findings - The results of this study indicate that the proportion of the board of commissioners has a positive effect on firm value, while green innovation and carbon emission disclosure do not significantly influence firm value. Firm size moderates the relationship between green innovation and firm value but does not moderate the relationships between the proportion of the board of commissioners, carbon emission disclosure, and firm value. Research limitations/implications - This study also provides insights for firm management and stakeholders regarding the factors influencing firm value and strategies for improvement in the future